THE PHENOMENON OF JOB HOPPING AMONG GENERATION Z: AN EXPLORATION THROUGH GROUNDED THEORY - Rinta Agustiani Dwiputri; Rizki Agung Ramadani; Tiyanda Hanti Arum Kusuma; Jerry Heikal (Journal of Social and Economics Research, 2024)
Recently, the phenomenon of job hopping has become a hot topic in Human Resource Management. It refers to the tendency of individuals, especially Generation Z, to frequently switch from one job to another in a short period of time. A survey reported that 83% of 1,100 Gen Z respondents considered themselves "job hoppers". This study aims to analyze the factors influencing job hopping among Generation Z. A qualitative research method with a grounded theory approach was employed. Purposive sampling was used to select five Generation Z respondents aged 24-27 years old for in-depth interviews. The interview results yielded 29 codes categorized into eight categories and 3 themes: career development path, work environment, and well-being. The work environment theme had highest score of 13, indicating that it is the primary factor influencing Generation Z's decision to switch jobs frequently.